Identifying Barriers to the Acquisition of Knowledge about Skin Integrity Impairment in Nursing Students: An Educational Intervention - Javier Sánchez-Gálvez; Santiago Martínez-Isasi; Miriam Sánchez-Hernández; Eva Vegue-Parra; Tamara Rafaela Yacobis-Cervantes; Francisco Mateo-Ramírez; Daniel Fernández-García (MDPI AG, 2024)
Background: Wound healing competence is implied in the nursing profession, but there is no standardized content regulation for wound care in university curricula. The primary objective of this study was to identify the barriers to the acquisition of knowledge about skin integrity impairment. Methods: A quasi-experimental pre-test and post-test study with an ad hoc questionnaire involved 304 students (control: 165; intervention: 139) from June to July 2023. A 10-h educational intervention focused on skin integrity assessment and treatment was conducted. Results: The control group, scoring 17 ± 0.22 out of a maximum of 61, achieved a significantly lower final test score (p < 0.001) compared to the wound care educational intervention group, with the pre-test group scoring 30 ± 0.76 and the post-test group scoring 43 ± 0.61. The educational intervention in wound care program improved nursing students' knowledge of prevention, assessment/diagnosis, treatment, lower limb wounds, and wound bed preparation by replacing the number of "Don't know" answers in the post-test group with correct answers. Conclusions: The barriers identified to the acquisition of knowledge about skin integrity impairment in nursing studies are the following: the transversality of teaching, the teaching and evaluation system, and the variability in the training of professionals and teachers in charge of their education. The educational intervention can be used to consolidate knowledge and to enhance students' self-confidence in caring for patients with wounds.